2006
DOI: 10.1101/gad.1455706
|View full text |Cite
|
Sign up to set email alerts
|

The Myc-dependent angiogenic switch in tumors is mediated by interleukin 1β

Abstract: Although induction of blood vessel growth is acknowledged as a pivotal requirement for the evolution of macroscopic tumors, the events that trigger onset of tumor angiogenesis remain largely obscure. The pervasive Myc oncoprotein is itself a potent inducer of angiogenesis in a wide range of tissues. We have used a reversibly switchable mouse transgenic model of Myc-dependent ␤-cell carcinogenesis to delineate the kinetics and causal sequence of angiogenic processes following acute Myc activation. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
142
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(152 citation statements)
references
References 49 publications
8
142
0
Order By: Relevance
“…Therefore, both studies underline the importance of c-Myc levels for intestinal tumour progression and there may be multiple key tumour-promoting mechanisms that c-Myc impinges on. This link between Myc and angiogenesis had been observed previously in pancreatic islet tumour growth driven by c-Myc overexpression and appears dependent on changes in c-Myc levels within the epithelial cells (Shchors et al, 2006).…”
supporting
confidence: 75%
“…Therefore, both studies underline the importance of c-Myc levels for intestinal tumour progression and there may be multiple key tumour-promoting mechanisms that c-Myc impinges on. This link between Myc and angiogenesis had been observed previously in pancreatic islet tumour growth driven by c-Myc overexpression and appears dependent on changes in c-Myc levels within the epithelial cells (Shchors et al, 2006).…”
supporting
confidence: 75%
“…Recent studies also indicated that VEGF expression levels are also controlled by c-Myc (Barr et al 2000, Knies-Bamforth et al 2004 and that c-Myc is essential for angiogenesis (Baudino et al 2002). Other studies have revealed that c-Myc plays a central role in the angiogenic switch in tumors (Knies-Bamforth et al 2004, Shchors et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…In a mouse transgenic model of Myc-dependent b-cell carcinogenesis, the onset of endothelial cell proliferation was noted to begin shortly after Myc-induced cell cycle entry of pancreatic b cells. Subsequent endothelial proliferation was not caused by local tissue hypoxia but through the release of pre-existing sequestered VEGF from the ECM by MMPs mediated by the production and release of the proinflammatory cytokine IL-1b (Shchors et al, 2006).…”
Section: Oncogene-mediated Angiogenesismentioning
confidence: 99%